Systematic review of psychological and social outcomes of adolescents undergoing bariatric surgery, and predictors of success. Issue 5 (6th November 2015) - White, B.; Doyle, J.; Colville, S.; Nicholls, D.; Viner, R. M.; Christie, D.
Summary: The psychological and social outcomes of bariatric surgery in adolescents, together with psychological and social predictors of success, were systematically reviewed. PubMed, EMBASE, ISI Web of Science and PsychInfo were searched on July 2014. Existing data were sparse; 15 were suitable for qualitative review and six for meta‐analysis (four quality of life [QOL], two depression). One study was a randomized controlled trial. A total of 139 subjects underwent Roux‐en‐Y gastric bypass, 202 underwent adjustable gastric band and 64 underwent sleeve gastrectomy. Overall QOL improved after bariatric surgery, regardless of surgical type with peak improvement at 6–12 months. Meta‐analysis of four studies showed changed in overall QOL at latest follow‐up of 2.80 standard deviation (SD) (95% confidence interval [CI] 1.23–4.37). Depression improved across all studies, regardless of procedure (effect size −0.47 SD [95% CI −0.76, −0.18] at 4–6 months). Two cohorts reported changes in both overall QOL and depression following a quadratic trajectory, with overall improvement over 2 years and deterioration in the second post‐operative year. There were limited data on other psychological and social outcomes. There were insufficient data on psychosocial predictors of outcome to form evidence‐based recommendations for patient selection for bariatric surgery at this time.